Application of Fresnel Prism in the Complex Treatment of Friendly Strabismus - V. N. Kurochkin; T. V. Terekhova; Y. D. Glumskova; Y. I. Triludina; O. A. Shelikhova (Oftalʹmologiâ)
Purpose: To analyze the effectiveness of Fresnel prism in the complex treatment of friendly strabismus.Patients and methods. The main group consisted of 428 patients with strabismus, who were assigned Fresnel prisms in combination with pleoptoorthoptic and surgical treatment. Indication for the appointment of Fresnel prism with a friendly strabismus was: angle of strabismus to 25 degrees, postoperative residual angles. The age of the patients ranged from 4 to 60 years. We evaluated the visual acuity without correction and with correction, refraction, character of vision, ability to bifoveal fusion evaluated with synoptophore. The results were compared with a control group treated without Fresnel prisms.Results. During initial selection of Fresnel prisms, doubling was revealed in 73% cases. With the constant wearing of glasses with Fresnel prisms, in which the state of orthotropy is achieved, in most patients doubling was cupped in the period from 2 weeks to 3 months. During the first month, doubling stopped in 72% of patients, and the minimum periods for arresting double vision were noted in preschool children. The absence of doubling served was an indication for surgical correction of strabismus. After the surgery, a good cosmetic effect was achieved in 392 persons (97%), and the state of orthotropy was in 330 of people (81.7%). Doubling after the operation was not observed, there was no relapse of strabismus. Comparative analysis of the main and control groups showed that in the main group of patients the use of prisms combined with pleoptoorthoptic and surgical treatment made it possible to restore binocular vision in 32.9% of cases.Conclusion. The use of Fresnel prism in the complex treatment of friendly strabismus in children allows to obtain not only a good cosmetic effect, but also to develop binocular vision in 32.9% of cases. The use of Fresnel prisms in the preoperative period in adults allows avoiding postoperative double vision, thereby reducing the risk of recurrence of strabismus because of the development of mechanisms for the formation of a single binocular image.